2018
DOI: 10.3389/fmicb.2018.02273
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus and β-Lactams: Emerging Insights and Potential Opportunities

Abstract: β-lactams, the most widely used class of antibiotics, are well-tolerated, and their molecular mechanisms of action against many bacteria are well-documented. Mycobacterium abscessus (Mab) is a highly drug-resistant rapidly-growing nontuberculous mycobacteria (NTM). Only in recent years have we started to gain insight into the unique relationship between β-lactams and their targets in Mab. In this mini-review, we summarize recent findings that have begun to unravel the molecular basis for overall efficacy of β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 101 publications
1
34
0
Order By: Relevance
“…Recent studies suggest that combining different classes of ␤-lactams against MABC members (30,33) and other bacteria (34,35) may be synergistic due to targeting a wider spectrum of enzymes that appear to be uniquely relevant to synthesis of peptidoglycan in MABC organisms (36,37). For example, Kumar et al recently demonstrated synergy between doripenem and cefdinir against MABC strains (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that combining different classes of ␤-lactams against MABC members (30,33) and other bacteria (34,35) may be synergistic due to targeting a wider spectrum of enzymes that appear to be uniquely relevant to synthesis of peptidoglycan in MABC organisms (36,37). For example, Kumar et al recently demonstrated synergy between doripenem and cefdinir against MABC strains (30).…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Recent evidence suggests that dual βlactam therapy may be more effective than using a single β-lactam. 16 In this study, MABC isolates were assessed for susceptibility to various antimicrobials, and the relationship between the erm(41) gene and inducible CLA resistance in each subspecies of MABC was explored. The results provide guidance for the empirical therapy of RGM infections.…”
Section: Introductionmentioning
confidence: 99%
“…The recent recognition of macrolide resistance has further narrowed treatment options (2). Combination drug regimens, which may include a β-lactam, aminoglycoside, macrolide, linezolid, or tigecycline, are routinely prescribed, but fewer than one-half of patients with pulmonary disease achieve sputum culture conversion (6, 7). Regrettably, treatment failures and recurrences are frequently reported (79).…”
Section: Introductionmentioning
confidence: 99%